2022
DOI: 10.1177/09564624211064133
|View full text |Cite
|
Sign up to set email alerts
|

Recent insights suggest the need for the STI field to embrace a more eco-social conceptual framework: A viewpoint

Abstract: A large number of countries are being confronted with twin epidemics of increasing STI incidence and antimicrobial resistance (AMR). This has led to calls to intensify STI screening of high STI prevalence populations. The available evidence suggests that this will have little impact on STI prevalence but a significant deleterious effect on AMR. We suggest that this call to intensify STI screening is one of the several errors that stem from the way that the STI-field has been dominated by a biomedical individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 114 publications
0
14
0
Order By: Relevance
“…16,29 As previous literature suggests, this is likely due to the fact that while 3-monthly screening may reduce prevalence/transmission in the short term, it is not addressing key drivers such as changing sexual practices such as decreased condom usage and dense sexual networks that are maintaining STIs at their endemic state in the MSM community. 24,43 Our participants suggested that acceptability of a change in screening frequency is possible with transparent communication delivered by a trusted healthcare professional.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…16,29 As previous literature suggests, this is likely due to the fact that while 3-monthly screening may reduce prevalence/transmission in the short term, it is not addressing key drivers such as changing sexual practices such as decreased condom usage and dense sexual networks that are maintaining STIs at their endemic state in the MSM community. 24,43 Our participants suggested that acceptability of a change in screening frequency is possible with transparent communication delivered by a trusted healthcare professional.…”
Section: Discussionmentioning
confidence: 99%
“…25 Instead, the high prevalence of STIs in the MSM community is likely linked to sexual network connectivity. 24,25 Intensive screening in MSM on PrEP has resulted in very high consumption levels of azithromycin and ceftriaxone. 15 Both are broad-spectrum antibiotics that can also cause resistance in other non-STI organisms and, according to the WHO, should be reserved for infections where there is clear evidence of benefit, and no alternatives exist.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Undoubtedly, STI testing is important among GBM to reduce time between infection and treatment, and to disrupt chains of transmission. Conversely, it has been argued that frequent universal screening of GBM may not be feasible or cost-effective for clinics, and even in context with increased STI testing among GBM, STI prevalence did not necessarily decrease at the population level 9,33 . In particular, Williams et al 34 argued that reducing asymptomatic screening for chlamydia and gonorrhea may have potential benefits to address growing antimicrobial resistance and burden on health care services, but should also be considered against potential harms from reduced screening.…”
Section: Discussionmentioning
confidence: 99%